2014
DOI: 10.1097/iae.0000000000000014
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Properties of 2% Lidocaine and Reduced Rate of Endophthalmitis After Intravitreal Injection

Abstract: Application of subconjunctival 2% lidocaine/0.1% methylparaben for anesthesia may reduce the incidence of endophthalmitis after IVT injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
1
14
0
2
Order By: Relevance
“…Even though masks are not used, talking during the procedure is avoided, as supported by previous studies that showed that wearing masks and avoiding talking had a similar reduction in bacterial contamination [25, 26]. In addition, our case of endophthalmitis did not receive subconjunctival anesthesia, but there are data suggesting that subconjunctival lidocaine 2% can have antibacterial properties and reduces the rate of infectious endophthalmitis [27]. Finally, pre and postinjection antibiotics are not routinely used in our practice, supported by data suggesting that the use of antibiotics does not lower the incidence of endophthalmitis and may contribute to development of a drug-resistant conjunctival flora [22, 23].…”
Section: Discussionsupporting
confidence: 65%
“…Even though masks are not used, talking during the procedure is avoided, as supported by previous studies that showed that wearing masks and avoiding talking had a similar reduction in bacterial contamination [25, 26]. In addition, our case of endophthalmitis did not receive subconjunctival anesthesia, but there are data suggesting that subconjunctival lidocaine 2% can have antibacterial properties and reduces the rate of infectious endophthalmitis [27]. Finally, pre and postinjection antibiotics are not routinely used in our practice, supported by data suggesting that the use of antibiotics does not lower the incidence of endophthalmitis and may contribute to development of a drug-resistant conjunctival flora [22, 23].…”
Section: Discussionsupporting
confidence: 65%
“…In a retrospective series, Tustin et al reported a rate of endophthalmitis of 8/8,189 (0.1%) when subconjunctival lidocaine was not used, compared with 0/6,853 when it was used (P = 0.03), suggesting that the use of subconjunctival anesthetic may reduce the risk of endophthalmitis [143]. However, 14 culture-negative cases of “possible” endophthalmitis were excluded, nine of which were after injection of triamcinolone and five after bevacizumab.…”
Section: Reviewmentioning
confidence: 99%
“…However, 14 culture-negative cases of “possible” endophthalmitis were excluded, nine of which were after injection of triamcinolone and five after bevacizumab. The same authors found that 2% lidocaine/0.1% methylparaben demonstrated rapid bactericidal effects against S. aureus , S. epidermidis and S. viridans in vitro [143]. …”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Subconjunctival lidocaine may play a role in the low endophthalmitis rates observed in our study; however, this is not explicitly stated in the 2014 recommendations by Avery et al 23. Tustin et al performed in vitro experiments to determine the antibacterial properties of 2% lidocaine/0.1% methylparaben (lidocaine) against causative organisms of endophthalmitis ( Staphylococcus aureus , S. epidermidis and Streptococcus viridans ) 24. Lidocaine demonstrated rapid bactericidal effects against all three organisms.…”
Section: Discussionmentioning
confidence: 55%